Utilizing diverse cross-sectional assessment templates to instruct novice nurses in the neurology department about typical diseases - Qing-Mei Wang; Dong-Ping Shi; Shi-Jing Zhang (Annals of Medicine)
Objective The aim of this study is to explore the utilization of diverse cross-sectional assessment templates for typical diseases in educating novice nurses in neurology departments.Methods Between January and December 2019, all registered nurses who had worked for less than 10 years at our center, were enrolled in this retrospective study. They were divided into the observation (18 nurses) and control (17 nurses) groups. The control group received training on various cross-sectional assessments for typical diseases. A comparative analysis was conducted on clinical work ability, nursing quality, adverse events, and patient satisfaction between the two groups.Results A total of 35 nurses participated in this study. The work ability score for nurses in the observation group was 97.42 ± 2.02 points, demonstrating a significant increase compared to the control group (92.17 ± 1.72 points) (p < 0.001). Regarding the quality of care provided to critically ill patients, the observation group demonstrated a significantly higher score of 95.82 ± 1.31 points compared to the control group, which scored 87.70 ± 3.15 points (p < 0.001). The number of adverse events within one year after admission was notably lower in the observation group, with 8 cases, compared to 23 cases in the control group (p = 0.006). Additionally, nurses in the observation group achieved a higher patient satisfaction score compared to the control group (97.23 ± 1.78 vs. 92.19 ± 1.49 points, p < 0.001).Conclusion The utilization of diverse cross-sectional assessment templates and instructional videos for typical diseases in the training of novice nurses in the neurology department enhanced nursing quality, improved clinical practical abilities, and improved patient safety.